ANALISIS KUALITAS TEKNIS DAN KUALITAS FUNGSIONAL PADA PERUSAHAAN SOLUTION PROVIDER DI JAKARTA - Farida Jasfar (Media Riset Bisnis & Manajemen, 2001)
This research is designed to examine the dimenslon of service quality, speciically applied technical and functional quality insolution provider companies in Jakarta. This research also alms to detemine the dimensions of service quality by com- paring the SERVQUAL of Parasuraman, Zeitharml and Berry (1985), Gronroos (1990), and Lapierre (1996). The degrees of service quality based on technical and functional quality were measured by using the Likert scale, and a data analysis method by employing confimatory factor analysis. The research findings disclosed that there are significant dimensions in service quality based on technical and functional quality. For the technical quality dimen- sion, reliability and trust are more significant than other dimensions. However, conceming the different findings functional quality dimension based on sales, and the whole variable (reliability and trust, attitude and behavior, accessibility and flex- ibility, and consumer participation) were significant, except the recovery variable. Finally, the functional quality dimension, based on maintenance and the whole variable (reliability and trust, attitude and behavior, recovery, accessibility and flex- ibility, and consumer participation) was significant.